A Protocol for Structured Robustness Reproductions and Replicability Assessments - Jörg Ankel-Peters; Abel Brodeur; Anna Dreber Almenberg; Magnus Johannesson; Florian Neubauer; Julian Rose (Institute of Labor Economics (IZA), 2025)
Robustness reproductions and replicability discussions are on the rise in response to concerns about a potential credibility crisis in economics. This paper proposes a protocol to structure reproducibility and replicability assessments, with a focus on robustness. Starting with a computational reproduction upon data availability, the protocol encourages replicators to prespecify robustness tests, prior to implementing them. The protocol contains three different reporting tools to streamline the presentation of results. Beyond reproductions, our protocol assesses adherence to the pre-analysis plans in the replicated papers as well as external and construct validity. Our ambition is to put often controversial debates between replicators and replicated authors on a solid basis and contribute to an improved replication culture in economics.
Keywords: A11; C18; 330; research transparency; robustness; reproducibility; replication; meta-science